Square root in secondary school - Matos, Zoltán (Teaching Mathematics and Computer Science, 2019)
Although in Hungary, for decades, the calculation method of the square root of a real number is not in the mathematics curriculum, many of the taught concepts and procedures can be carried out using different square root finding methods. These provide an opportunity for students in secondary school to practice and deepen understand the compulsory curriculum. This article presents seven square-root- nding methods, currently teachable in secondary schools. Subject Classification: A33, A34, F53, F54